Exosomes in triple negative breast cancer: Garbage disposals or Trojan horses?. (31st March 2020) - Goh, Chia Yin; Wyse, Cathy; Ho, Matthew; O'Beirne, Ellen; Howard, Jane; Lindsay, Sinéad; Kelly, Pamela; Higgins, Michaela; McCann, Amanda
Abstract: Triple negative breast cancer (TNBC) is a breast cancer subtype which is particularly aggressive and invasive. The treatment of TNBC has been limited due to the lack of well-defined molecular targets. Exosomes are nano-sized extracellular vesicles that are released from virtually all cell types into the extracellular space. Due to their endocytic origin, exosomes carry valuable information from their cells of origin. Exosomes were first thought to serve as " garbage disposals " that eliminate unwanted cellular components. Later, they were found to be involved in the pathology of many diseases including cancer. Despite their established roles in multiple diseases, only a small number of studies have focused on the role of exosomes in TNBC. In this review, we outline the roles of exosomes in cancer progression, metastasis and drug resistance in this breast cancer subtype. We then further illustrate the potential roles of exosomes as diagnostic tools, therapeutic targets and delivery systems.